Leptospira pada Tikus dan Badan Air serta Riwayat Penularan Penderita di Daerah Baru Kasus Leptospirosis di Bantul - Zumrotus Sholichah; Bondan Fajar Wahyudi; Corry Laura Junita Sianturi; Novia Tri Astuti (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2021)
In 2017 leptospirosis cases occur in new areas in Bantul where cases have never been previously reported. Cases still occur in 2018 with an interval of two months after the first case. Preventive and curative efforts in the context of controlling cases have been carried out by the local health office, in addition to these control efforts, it is also necessary to know the presence of Leptospira in rats and water bodies in the area as well as the history of patients transmission. This study was conducted to provide epidemiological data, especially the status of Leptospira in rats as reservoir animal and water bodies as well as a history of patient activity as basic data for leptospirosis control in Gilangharjo Village. This cross-sectional study was conducted at the case location in RT 03 Jodog, Gilangharjo Village, Pandak District, Bantul Regency, which was conducted in April 2018. Leptospira infection status was carried out on rats and water bodies by molecular examination, while the history of transmission based on interviews with patients and the result of the examination of Leptospira status. Rat species caught were dominated by R.tanezumi, R. norvegicus and B. indica. Positive rat infected with Leptospira were found in B. indica while in water bodies Leptospira contamination was not found. Infected rat can be a source of transmission for humans and other animals. Most of the patient's activities were carried out in the fields and at home, all of the patients had wounds that were not treated, and had a history of contact with rats that might transmit Leptospira to humans.